Vectorial signalling mechanism required for cell-cell communication during sporulation in Bacillus subtilis - Verónica Diez (2011)
Spore formation in Bacillus subtilis takes place in a sporangium consisting of two chambers, the forespore and the mother cell, which are linked by pathways of cell-cell communication. One pathway, which couples the proteolytic activation of the mother cell transcription factor sigma E to the action of a forespore synthesized signal molecule, SpoIIR, has remained enigmatic. Signalling by SpoIIR requires the protein to be exported to the intermembrane space between forespore and mother cell, where it will interact with and activate the integral membrane protease SpoIIGA. Here we show that SpoIIR signal activity as well as the cleavage of its N-terminal extension is strictly dependent on the prespore fatty acid biosynthetic machinery. We also report that a conserved threonine residue (T27) in SpoIIR is required for processing, suggesting that signalling of SpoIIR is dependent on fatty acid synthesis probably because of acylation of T27. In addition, SpoIIR localization in the forespore septal membrane depends on the presence of SpoIIGA. The orchestration of sigma E activation in the intercellular space by an acylated signal protein provides a new paradigm to ensure local transmission of a weak signal across the bilayer to control cell-cell communication during development.